Factors affecting employee job performance in Ranhill SAJ Sdn Bhd / Siti Nuradlina Jamaludin - Jamaludin, Siti Nuradlina (Faculty of Business and Management, 2019)
Job performance has been one of the most primary dependent variables that many researchers studied for a long decade. This study focused to examine factor that influence to employee job performance in Ranhill SAJ Sdn Bhd in Segamat district. Out of 175 of total employee, 118 employee that work in Ranhill SAJ Sdn Bhd in Segamat district has been selected as a sample size in this study. The objective of this research is to examine the correlation between organizational communication, training and development and workplace environment with employee job performance and to identify the rank of the dominant factor that influence to the job performance of employee in Ranhill SAJ Sdn Bhd. In this study the researcher uses convenient sampling technique and a total of 118 questionnaire survey was distributed. Pilot study was done as a test, and it was found that the internal consistency reliability of the measure used in the pilot study is acceptable. The researcher use Statistical Package for Social Sciences (SPSS) to process the data. The result of the data analysis have also concluded the four research objectives. The data shows that the hypothesized is accepted and the strength of the correlation between organizational communication, training and development and workplace environment with employee job performance has moderate and positive relationship. Furthermore, training and development is found to have the highest significant relationship on job performance followed by organizational communication and then workplace environment.